High‐intensity focused ultrasound focal therapy for prostate cancer. Issue 3 (4th June 2020) - Reddy, Deepika; Dudderidge, Tim
Abstract : Focal therapy for prostate cancer delivered with high‐intensity focused ultrasound offers benefits such as fewer side‐effects than some other treatments. Ongoing trials will help inform how the therapy can be best used but in the meantime the authors argue for increased availability for suitable men.